The impact of varying tract turning angle on fibre tractography reconstruction and diffusion tensor imaging indices - Tokemin, Nur’ain Nurjannah (Universiti Sains Malaysia, 2016)
Impact of varying turning angle in fibre tractography reconstruction was evaluated. Diffusion tensor images were obtained retrospectively from Nordiclce (version 2.3.9, Nordic Neuro Lab) database available in AMDI-USM. All data were acquired using GE 1.5 Tesla MRI system (Signa HDxt, GE Healthcare). A healthy female subject with no associated neurological or brain illness participated in the study. DTI post processing was performed in which DTI parametric maps and fibre tractography were reconstructed. During fibre tracking, tract turning angle was varied for 25°, 35°, 45° (default turning angle set by software developer), 55° and 65°. Then, the assessment was performed on DTI indices including fractional anisotropy (FA), mean diffusivity (MD) as well as number of fibres reconstructed. The values obtained for each angle were compared with that of obtained using default angle. Tractographies of coipus callosum (CC) and corticospinal tract (CST) were initiated by placement of single seed region of interest (ROI) on CC, cerebral peduncle and centrum semiovale at superior part of brain. Results obtained showed modification of turning angle from its default value has less impact on CC. There were no differences in FA noted between the default angle with angle 35°, 55° and 65°. Besides, MD showed decreases in percentage difference as the turning angle became large. Similar to number of fibres which exhibited decrease in percentage from 8.4% at smallest angle to 3% at the largest angle. However, the differences were not too significant. While for CST, small differences were noted at 35° and 55°. Whereas larger percentage difference was found at 25° with 5.4%, 1.44% and 30.3% for FA, MD and number of fibres respectively. Followed by 65° with 1.62%, 0.19% and 16.2% for FA, MD and number fibres respectively. In conclusion, the modifications of tract turning angle do give impact on reconstruction of CST fibre bundle while lesser impact was seen on CC fibre bundles.